Semantic difficulties of the English aerospace terminological system - Irina Suima (Challenges and Issues of Modern Science)
The Purpose of the research is to describe the modern system of astronomical and rocket engineering terminology and to investigate the peculiarities of the translation of the relevant terms into the Ukrainian language. Research Methods: methods of linguistic analysis, descriptive and comparative methods, methods of classification and systematization. Findings: The aerospace terminological system does not exist separately from the terminological systems of other industries. The main method of translating a term is using a lexical equivalent. The following methods of translation of terminological units are also distinguished: descriptive translation, translation using the genitive case, translation using prepositions, literal translation, transcription, transliteration. Multi-component terms cause the greatest difficulty in translation. Difficulties arise mostly when translating terms contain five or more components. Theoretical Implications: Aerospace terminology is analyzed as a combination of a certain concept, object or phenomenon that exists in reality, and its verbal expression. The term is described as an element of polycode text and it acquires certain structural and functional features, depending on the environment in which it functions. Practical Implications are determined by the fact that the results of the studies can be used for the study of the terminology of technical and humanitarian industries. Originality: An advanced study of the specialized astronomical and rocket engineering vocabulary contributes to a more complete disclosure of the leading trends in the development of national terminology, and the study of the peculiarities and difficulties of its translation will allow to determine modern functional and stylistic trends within the given field and predict its future prospects. Research Limitations include the study of basic terminative morphemes and structural models of terms that determine the specificity of term formation in the aerospace industry; the study of semantic and structural features of English-language aerospace terms.